KEBIJAKAN PEMANFAATAN MEDIA SOSIAL DINAS PERPUSTAKAAN & KEARSIPAN SURABAYA - Rio Febriannur Rachman; Kacung Marijan (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
The City Government of Surabaya is one of the pioneers of public services based on information and communication technology. All regional apparatuses in this city are competing to create electronic applications to realize the efficiency and effectiveness of work programs. This study discusses how technology-based policies, especially in the field of social media utilization, conducted by the Surabaya Library and Archives Service, were made and implemented to optimize public services. Theory of technology determination and public policy are used as a foundation for thinking in studies. The research in this study uses a qualitative method with a descriptive approach. Data collection was carried out through in-depth interviews to the three informants, observing on social media, and reading some literatures and other documents about the research topic. The analysis technique is done through data reduction, data presentation, and formulation of conclusions. This study shows that the use of social media at the Surabaya Library and Archives Office has been going well and has had a positive impact. The implementation of this public policy is also in line with the formulation of sustainable development goals, outlined by the United Nations. However, there needs to be a reform in a number of aspects, including the addition of frequency of content updates on social media. Adding content can be one way to build closeness between the goverment and the community. In addition, increasing the number of collaborative partners in social media-based programs is also needed to optimize public services.